Small Cell Technology in Heterogeneous Wireless Mobile Networks of Future Smart Cities - Mohammad R. Kadhum; Heba Haboobi (International Journal of Computers and Informatics, 2026)
In this paper, the use of intelligent heterogeneous mobile networks in congested smart cities, where macro, micro, pico, and femto cells are smartly monitored, is examined. The study demonstrates, from a physical-layer standpoint, the key benefits of deploying smart-driven small cells, including coverage area, transmission throughput, and resource consumption. The proposed design employs progressive intelligent software solutions to enable smart coordination among the installed base stations via the used waveform. By adopting both advanced cell technologies and smart applications, a developed communication system for future smart cities can be realized. Accordingly, the smart control of the presented scheme achieves lower battery usage, higher throughput, and wider transmission. Specifically, the offered solution is applied to crowded cities around the world, particularly the capitals and tourist cities, where millions of people visit each year. To verify the system performance of our advanced, smart, and effective solution, the transceiver systems at the explored locations were investigated before and after peak times using MATLAB.